2014
DOI: 10.1681/asn.2013060588
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Glucose Metabolism, Osmotic Stress, and Sodium-Glucose Cotransporter Isoform-Mediated Transport on Na+/H+ Exchanger Isoform 3 Activity in the Renal Proximal Tubule

Abstract: Na + -glucose cotransporter 1 (SGLT1)-mediated glucose uptake leads to activation of Na + -H + exchanger 3 (NHE3) in the intestine by a process that is not dependent on glucose metabolism. This coactivation may be important for postprandial nutrient uptake. However, it remains to be determined whether SGLTmediated glucose uptake regulates NHE3-mediated NaHCO 3 reabsorption in the renal proximal tubule. Considering that this nephron segment also expresses SGLT2 and that the kidneys and intestine show significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 66 publications
7
120
0
4
Order By: Relevance
“…Na + /H + -exchanger 3 (NHE3) is an early proximal tubule transporter that is co-expressed with SGLT2. Inhibition of SGLT2 may also inhibit NHE3 as recently proposed [2, 40]. This interaction between SGLT2 and NHE3 could be relevant to the blood pressurelowering effect of SGLT2.…”
Section: How Can Sglt2 Inhibitors Protect the Kidney And Heart In Typmentioning
confidence: 65%
“…Na + /H + -exchanger 3 (NHE3) is an early proximal tubule transporter that is co-expressed with SGLT2. Inhibition of SGLT2 may also inhibit NHE3 as recently proposed [2, 40]. This interaction between SGLT2 and NHE3 could be relevant to the blood pressurelowering effect of SGLT2.…”
Section: How Can Sglt2 Inhibitors Protect the Kidney And Heart In Typmentioning
confidence: 65%
“…41 A recent paper reported that activating the Na/ glucose cotransporter (presumably SGLT2, which is colocalized with NHE3) by adding 5 mM glucose in the lumen of rat proximal tubules can upregulate the Na/HCO 3 transport mediated by NHE3. 42 More interestingly, in the total absence of luminal glucose, addition of luminal Pz produced a clear inhibition of NHE3 activity. This unexpected observation could be explained if SGLT2/MAP17 and NHE3 are part of a "signaling platform" held together by the scaffolding protein PDZK1.…”
Section: Discussionmentioning
confidence: 92%
“…These data suggest that a compensatory increase in NHE3 activity is elicited by luseogliflozin-induced increases in sodium and water load at the proximal tubules. Conversely, recent studies have shown that NHE3 colocalizes with SGLT2 and that the nonselective SGLT2-inhibitor phlorizin can inhibit NHE3 function [37]. The reason for these discrepant data is not clear, but could be explained by differences in the animal model (SHRcp vs. normal Wistar rats), experimental setup (chronic vs. acute administration) or specificity for the SGLT2 inhibitor (luseogliflozin vs. phlorizin).…”
Section: Expression Of Major Sodium Transporters In Kidneymentioning
confidence: 94%